Microbial Succession and Chemical Characteristics in Fermentation of Ambonese Arrack (Sopi), Traditional Beverage from Maluku - Ferymon Mahulette; Dea Indriani Astuti (Biosaintifika: Journal of Biology & Biology Education, 2020)
Ambonese arrack is one of the traditional fermented beverage product in Maluku, Indonesia. The microbiological research of this beverage that is processed using coconut sap as raw material has never been done before. The research aimed to analyze the microbial succession and chemical characteristics during fermentation of Ambonese arrack. The sample of coconut sap was taken from traditional producer in Mahia village, Ambon. The dominant microbes in the fermentation of Ambonese arrack were Pichia polymorpha and Kloeckera javanica. The highest numbers of these two microbes was obtained after 15 hours fermentation (9.6 log Cfu/mL and 9.9 Cfu/mL, respectively). The sugar content decreased from 593.3 mg/L to 474.3 mg/L, whereas ethanol content increased from 0.0018 g/L to 0.0100 g/L. The pH value decreased from 4.70 to 3.10. The research has isolated indigenous microbes in Ambonese arrack fermentation which was considered as novelty. The bacteria that play a role in fermentation can be used as a starter in the fermentation of various beverage products, especially Ambonese arrack. The results of this research can improve the quality of this fermentation product in the future.